Simultaneous Parasympathetic and Sympathetic Activation Reveals Altered Autonomic Control of Heart Rate, Vascular Tension, and Epinephrine Release in Anesthetized Hypertensive Rats - Berg, Torill; Jensen, Jørgen (Frontiers in Neurology, 2011)
Sympathetic hyperactivity and parasympathetic insufficiency characterize blood pressure control in genetic hypertension, but is difficult to demonstrate experimentally in anesthetized rats. Here we present a pharmacological approach to activate sympathetic and parasympathetic nerves simultaneously, and identify their contribution. Anaesthetized normotensive (WKY) and spontaneously hypertensive rats (SHR) were injected i.v. with 4-aminopyridine (4-AP), a voltage-sensitive K+ channel inhibitor. Blood pressure was recorded through a femoral artery catheter, cardiac output and heart rate (HR) through an ascending aorta flow probe. Total peripheral vascular resistance (TPVR) was calculated. 4-AP induced an immediate, atropine- and hexamethonium-sensitive bradycardia in WKY, and in strains, a subsequent, sustained tachycardia, and norepinephrine but not epinephrine release. The tachycardia was eliminated by reserpine, nadolol or right vagal nerve stimulation, but not adrenalectomy, scopolamine or hexamethonium. 4-AP-induced, atropine-sensitive bradycardia was observed in reserpinized or nadolol-treated SHR, where atropine also increased the late HR-response. 4-AP increased TPVR, transiently in WKY but sustained in SHR. Yohimbine but not phentolamine prevented TPVR down-regulation in WKY. Reserpine, phentolamine and prazosin eliminated the late vasoconstriction in SHR. Plasma epinephrine overflow increased in nadolol-treated SHR. Conclusions: 4-AP activated parasympathetic ganglion transmission and peripheral, sympathetic nerve norepinephrine release. The sympathetic component dominated the HR-response to 4-AP in SHR. α2-adrenceptor-dependent vasodilatation opposed norepinephrine-induced α1-adrenergic vasoconstriction in WKY, but not in SHR. A βAR-activated, probably vagal afferent mechanism, hampered adrenal epinephrine secretion in SHR. Thus, 4-AP exposed mechanisms, which contribute to hypertension, and may allow identification of the factors responsible.